qanda-logo
apple logogoogle play logo

Calculator search results

Formula
Solve the equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Graph
$3 x - y = 2$
$x$Intercept
$\left ( \dfrac { 2 } { 3 } , 0 \right )$
$y$Intercept
$\left ( 0 , - 2 \right )$
$3x-y = 2$
$x = \dfrac { 1 } { 3 } y + \dfrac { 2 } { 3 }$
$ $ Solve a solution to $ x$
$3 x \color{#FF6800}{ - } \color{#FF6800}{ y } = 2$
$ $ Move the rest of the expression except $ x $ term to the right side and replace the sign $ $
$3 x = 2 \color{#FF6800}{ + } \color{#FF6800}{ y }$
$3 x = \color{#FF6800}{ 2 } \color{#FF6800}{ + } \color{#FF6800}{ y }$
$ $ Organize the expression $ $
$3 x = \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 2 }$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 2 }$
$ $ Divide both sides by the same number $ $
$\color{#FF6800}{ x } = \left ( \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 3 }$
$x = \left ( y + 2 \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 3 }$
$ $ Convert division to multiplication $ $
$x = \left ( y + 2 \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
$x = \left ( \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
$ $ Multiply each term in parentheses by $ \dfrac { 1 } { 3 }$
$x = \color{#FF6800}{ \dfrac { 1 } { 3 } } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
$x = \dfrac { 1 } { 3 } y + \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
$ $ Calculate the product of rational numbers $ $
$x = \dfrac { 1 } { 3 } y + \color{#FF6800}{ \dfrac { 2 } { 3 } }$
$y = 3 x - 2$
$ $ Solve a solution to $ y$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } - y = 2$
$ $ Move the rest of the expression except $ y $ term to the right side and replace the sign $ $
$- y = 2 \color{#FF6800}{ - } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \right )$
$- y = \color{#FF6800}{ 2 } \color{#FF6800}{ - } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \right )$
$ $ Organize the expression $ $
$- y = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 2 }$
$\color{#FF6800}{ - } \color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 2 }$
$ $ Change the sign of both sides of the equation $ $
$y = 3 x - 2$
$ $ 그래프 보기 $ $
Linear function
Solution search results
search-thumbnail-$3x-4=2$ 
$3x-y=2$ $2x+y=7$ 
dir Ure dubrtitution 
method 
Rleare!
10th-13th grade
Other
search-thumbnail-coefficients: 
$1.$ $13+2y=9x$ 
$3y=7x$ 
$2$ $3x-y=23$ 
$\dfrac {x} {3}+\dfrac {y} {4}=4$
10th-13th grade
Other
search-thumbnail-$94.$ $2x-y=23$ 
$x-9=-1$
7th-9th grade
Algebra
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple logogoogle play logo